Evaluating the Concentration of Heavy Metals in Commercial Coffee: A Comparative Study with Global Safety Levels - Azza Hussien; Huda Saad; Kasem Abdinibi (AlQalam Journal of Medical and Applied Sciences, 2025)
Given that coffee represents a widely popular beverage, and given the harm that this drink can cause as a result of the accumulation of some heavy metals in it. This study aimed to concentrations of the accumulation of heavy metals in coffee beans, in addition to evaluating the concentration of some heavy metals,'' such as iron (Fe), Lead (Pb), chromium (Cr), copper (Cu) and essential minerals (sodium (Na), potassium (K)'' in different types of commercial coffee available in the Libyan market. Through a methodology based on analyzing the concentration of metals in 6 types of coffee widespread in the Libyan market and determining the concentration of metals in them, and comparing it to the internationally permissible percentage. The results indicated that most of the percentages are within the permissible limits, as Potassium concentrations were less than the permissible limits. Concentrations of (K) in the coffee samples reached between 0.01793 and 0.02193 parts per million, less than the permissible limit (0.07 ppm). As for Na concentration ranged between 0 and 0.00058 ppm, which is much less than the permissible limit (0.06 ppm). While the Cu concentration exceeded the permissible limit (0.02 ppm), which constitutes a threat to public health, as well as the Pb concentration ranged between 88.9015 and 132.983 ppm, exceeding the permissible limit (0.04 ppm). The concentration of Cr³ ranged between 5.4687 and 5.5886 ppm, exceeding the recommended daily dose (0.03 ppm).